Grain Yield and Nitrogen Use Efficiency of Late-cropping Rice in Response to Delayed Application of Nitrogen and Altered Plant Spacing in South China - Yanzhuo LIU; Kaiming LIANG; Junfeng PAN; Nongrong HUANG; Xuhua ZHONG (Guangdong nongye kexue, 2022)
【Objective】In order to further enhance grain yield of rice and nitrogen (N) use efficiency (NUE), N fertilizer was reduced and topdressing was delayed, together with alteration in row and plant spacing and planting density.【Method】In two late seasons, comparison trials were conducted with 8 treatments, including zero applied N (T1), farmers' practice (T2, control), 3 moderately-delayed N topdressing (T3-T5) and 3 highly-delayed N topdressing (T5-T8). T3-T8 also had alteration in N application rate, planting density and row and plant spacing.【Result】In comparison to T2, the average grain yields under T3-T5 were increased by 29.7% and 15.9%, and those of T6-T8 were increased by 26.4% and 18.6% in two late seasons, respectively. In both late seasons, nitrogen uptake and plant growth under T3-T5 and T6-T8 were slower before panicle initiation and they were both increased or accelerated thereafter. Based on average results in two late seasons, leaf area indexes at heading stage were enhanced by 8.5% and 11.8% respectively under T3-T5 and T6-T8 compared with that under T2. Leaf nitrogen contents at heading stage were enhanced by 16.8% and 23.5%, respectively. The numbers of panicles per hectare were increased by 14.5% and 15.2%, panicle size remained unchanged or was increased by 12.5%, sink sizes were increased by 13.6% and 29.3%, seed setting rate was enhanced by 9.0% or remained the same, 1000-grain weight remained identical or was decreased by 9.0%, biomasses were increased by 14.8% and 15.5%, and harvest indexes were increased by 7.2% and 6.4%, respectively. The total amounts of N uptake were increased by 27.6% and 40.7%, N uptake efficiencies were increased by 85.9% and 124.2%, agronomical efficiencies were increased by 99.1% and 102.5%, and partial factor productivity was increased by 32.1% and 36.2%, respectively. Additional N input, dense planting and alteration in row and plant spacing had little effect on yield and NUE. Highly-delayed N topdressing could further expand sink size and improve NUE, but could not enhance grain yield anymore.【Conclusion】With reduced N input, both source and sink of rice were substantially enlarged, and the yield and NUE were dramatically increased under moderately-delayed and highly-delayed N topdressing.